Frequency diversity improvement factor for rain fade mitigation in Malaysia - Islam, Md. Rafiqul; Altajjar, M. Laith; Mohammad Shawkat, Habib; Abdullah, Khaizuran (IEEE, 2015)
Microwave communication systems in tropical region like Malaysia, operating at higher frequency ranges, are degraded its performance severely during rains. Hence, the rain fade must be taken in consideration for the MW link design to track the service outage and quality. This paper aims to develop and propose frequency diversity Improvement Factor prediction model for rain fade mitigation from 5 – 40 GHz. The rain attenuation is predicted based on ITU-R rain attenuation prediction method using measured rain rate in Malaysia. The predicted data are analysed to develop and propose a prediction for the improvement factor. The proposed improvement factor model is investigated according to the fade margin where the frequency separation is set to 5 GHz only.